Find the derivative then make it into the format:
I got it to the form
Or have I done something wrong?
Follow Math Help Forum on Facebook and Google+
Not quite right --note you need the same power top and bottom
Note 49 -x^2 = (7-x) (7+x)
you have - [sqrt(x+7)/sqrt((7-x)] = - [(x+7)/(-x+7)]^(1/2)
n = 7
m = -1
Wouldn't I then currently have
I think I know where your going but I don't see it :S, Can you explain that?
x+7 = 7 + x
so (x+7)/[sqrt(7+x)sqrt(7-x)]=( 7 +x)/[sqrt(7+x)sqrt(7-x)]
OHh okay, thank you!
View Tag Cloud